2019
DOI: 10.3390/ijerph16245086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Critical Illness Insurance on Household Catastrophic Health Expenditure: The Latest Evidence from the National Health Service Survey in China

Abstract: Background: China fully implemented the critical illness insurance (CII) program in 2016 to alleviate the economic burden of diseases and reduce catastrophic health expenditure (CHE). With an aging society, it is necessary to analyze the extent of CHE among Chinese households and explore the effect of CII and other associated factors on CHE. Methods: Data were derived from the Sixth National Health Service Survey (NHSS, 2018) in Jiangsu Province. The incidence and intensity of CHE were calculated with a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…Additionally, this study showed that several key determinants, such as household size, receiving inpatient services, having members over 60 years old, economic status, geographic location, residency location, education, employment status, and self-rated health status, exerted an impact on economic protection, as reported in previous studies [ 28 , 29 , 50 ]. This study only regarded these influencing factors as control variables without detailed explanation.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, this study showed that several key determinants, such as household size, receiving inpatient services, having members over 60 years old, economic status, geographic location, residency location, education, employment status, and self-rated health status, exerted an impact on economic protection, as reported in previous studies [ 28 , 29 , 50 ]. This study only regarded these influencing factors as control variables without detailed explanation.…”
Section: Discussionsupporting
confidence: 81%
“…It was found that NCMS increased out-of-pocket medical expenditure by 12.3% [14], and it failed to prevent CHE and medical impoverishment [15]. In response to this situation, the Chinese government introduced, in 2016, the critical illness insurance (CII) program, which provides coverage to alleviate economic burdens among those with NCMS and URBMI coverage [36]. However, it is still unknown whether this program has achieved its intent [35].…”
Section: Discussionmentioning
confidence: 99%
“…By performing a face-to-face survey using an electronic tablet, the investigator inquired about all the members of each household one by one, filled in the related electronic questionnaires offline [13], and then uploaded the survey data online after the survey instructors examined the responses for each person. Because this study was a national survey project and was organized by the relevant departments of the government, the selected residents actively cooperated with the survey.…”
Section: Data Sourcementioning
confidence: 99%